Compostos de paládio(II) contendo acetofenonaoxima ortometalada: síntese, caracterização e avaliação da atividade citotóxica - Souza, Ronan Farias Freire de [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
Cyclometallated Pd(II) compounds are of great interest, specially, for their extensive applications in various science areas. Cyclopalladated compounds consist of a class of palladium(II) chelates with potencial medicinal uses since many of them exhibit antitumor activity comparable or superior to cisplatin (main atineoplastic agent) and significant antimycobacterial and antiprotozoal activities as well. In this context, the present work aimed at to synthesize fourteen novel cyclopalladated species of the type [Pd(X)(C2,N-afox)(X)(L)], where C2,N-afox = acetophenoneoxime, L = thiourea (tu); N-methylthiourea (mtu); N,N’-dimethylthiourea (dmtu); N-phenylthiourea (ftu); N,N’-diphenylthiourea (dftu); thioacetamide (taa) and thiobenzamide (tbz) and X = Cl- or I-. Their structures were proposed by C, H and N elemental analysis, thermal analysis (thermogravimetric and differential), infrared spectroscopy, 1H and 13C nuclear magnetic resonance spectroscopy. Single-crystal X-ray diffraction studies were carried out for [PdCl(C2,N-afox)(L)], where L = (tu), (dmtu) and (taa). The in vitro cytotoxic activity was evaluated against MRC-5 (human lung fibroblast), HepG2 (liver hepatocellular carcinoma), Cal27 (oral adenosquamous carcinoma), 4T1 (mammary carcinoma), B16F10-Nex2 (murine melanoma), A2058 (human melanoma) and Sk-Mel-110 / Sk-Mel-05 (human metastatic melanomas). The results showed that compounds with methyl and phenyl groups in the thiocarbonylated ligand tend to be more cytotoxic than cisplatin (standard drug) and the exchange of chloride by iodide in the palladium coordination sphere favored the compounds activity. Cell cycle assays were performed, revealing that the complexes act on the sub-G1 cycle phase and that the cells die in sub-G1/G1 without necessarily duplicate the DNA and hemolysis assays in healthy blood cells, indicating that chloro-complexes in general didn’t show significant hemolytic action. In addition, the incorporation of the chloro-complexes bearing (tu), (dmtu) and (dftu) into nanostructured lipid systems revealed that their selectivity against HepG2 increased three-fold compared to cisplatin, showing that the association of these lipid systems with palladium(II) compounds may be of interest in the cancer treatment.

Ciclometalados de paládio(II) são de grande interesse, sobretudo, por suas extensas aplicações em diversas áreas da ciência. Os compostos ciclopaladados constituem uma classe de quelatos de paládio(II) com potencial uso medicinal por apresentarem atividade antitumoral comparável ou superior à da cisplatina (principal agente antineoplásico), além de atividades antimicobacteriana e antiprotozoária. Nesse contexto, o presente trabalho objetivou sintetizar catorze ciclopaladados inéditos do tipo [Pd(X)(C2,N-afox)(L)], em que C2,N-afox = acetofenonaoxima, L = tiouréia (tu); N-metiltiouréia (mtu); N,N’-dimetiltiouréia (dmtu); N-feniltiouréia (ftu); N,N’-difeniltiouréia (dftu); tioacetamida (taa) e tiobenzamida (tbz) e X = Cl- ou I-. Suas estruturas foram propostas por análise elementar de C, H e N, análise térmica (termogravimétrica e diferencial); espectroscopia vibracional na região do infravermelho, espectroscopia de ressonância magnética nuclear de 1H e 13C. Estudos de difratometria de raios X de monocristal foram realizados para os compostos [PdCl(C2,N-afox)(L)], com L = (tu), (dmtu) e (taa). A atividade citotóxica in vitro foi avaliada frente às linhagens MRC-5 (fibroblasto de pulmão humano), HepG2 (carcinoma hepatocelular de fígado), Cal27 (carcinoma espinocelular oral), 4T1 (carcinoma mamário murino), B16F10-Nex2 (melanoma murino), A2058 (melanoma humano) e Sk-Mel-110  Sk-Mel-05 (melanomas metastático humano) demonstrando que os compostos contendo grupos metil e fenil no ligante tiocarbonilado, tendem a ser mais citotóxicos que a cisplatina (fármaco padrão) e que a troca de cloreto por iodeto na esfera de coordenação do paládio favoreceu a atividade dos compostos. Foram realizados ensaios de ciclo celular, revelando que os complexos atuam na fase sub-G1 do ciclo e que as células morrem em sub-G1/G1 sem haver necessariamente a duplicação do DNA e ensaios de hemólise em células sanguíneas saudáveis, indicando que os cloro-complexos em geral não apresentaram ação hemolítica significativa e, além disso, a incorporação dos cloro-complexos, contendo (tu), (dmtu) e (dftu), em sistemas lipídicos nanoestruturados revelou que a seletividade deles frente a HepG2 aumentou três vezes em relação a cisplatina, mostrando promissora a associação desses sistemas aos compostos de paládio(II) no tratamento de câncer.
Palladium(II) compounds containing orthometallated acetophenoneoxime: synthesis, characterization and cytotoxic activity evaluation
Keywords: Ciclopaladados; Oximas; Atividade antitumoral; Acetofenonaoxima; Ligantes sulfurados; Cyclopalladated; Oximes; Antitumor activity; Acetophenoneoxime; Sulfur ligands